CAR-T cell therapy in brain malignancies: obstacles in the face of cellular trafficking and persistence - Yaacoub, Serge; Vannoy, Elton; Maslova, Stefanyda; Haffey, Abigail; Khorsandi, Khatereh; Sheybani, Natasha; Haydar, Dalia (Frontiers in Immunology, 2025)
Chimeric Antigen Receptor T (CAR-T) cell therapy offers substantial promise for the treatment of brain malignancies, yet its clinical translation remains limited. Tumors such as Glioblastoma Multiforme (GBM), Diffuse Intrinsic Pontine Glioma (DIPG), and Medulloblastoma (MB) are associated with poor prognoses and exhibit limited responsiveness to conventional treatment modalities, including radiotherapy, chemotherapy, and surgical resection. The application of CAR-T cell therapy in these contexts faces significant challenges, primarily in terms of efficient cellular trafficking into the tumor microenvironment and access to heterogeneous tumor regions. Furthermore, CAR-T cell persistence, defined by the long-term survival and functionality of infused cells, remains a critical hurdle in achieving durable therapeutic responses and preventing tumor relapses. This review aims to address the two predominant barriers, trafficking and persistence, by discussing the underlying mechanisms that limit CAR-T cell efficacy in brain tumors, reviewing current strategies aimed at overcoming these challenges, and evaluating novel approaches to enhance the effectiveness of CAR-T therapies in this setting.